2014
DOI: 10.1016/j.tws.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on the quasi-static and dynamic crushing responses of multi-layer trapezoidal aluminum corrugated sandwiches

Abstract: a b s t r a c tThe axial crushing responses of bonded and brazed multi-layer 1050 H14 trapezoidal aluminum corrugated core (fin) sandwich structures, with and without aluminum interlayer sheets in 01/01 and 01/901 core orientations, were both experimentally and numerically investigated at quasi-static and dynamic strain rates. Multi-layering the core layers decreased the buckling stress and increased the densification strain. The experimental and simulation compression stress-strain curves showed reasonable ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Same is valid for the cylindrical portion. Kılıçaslan et al [8] were reported similar results for a confined corrugated core sandwich structure; which was also a progressively collapsing structure. In their study, as a result of confining, buckling and post buckling stresses increased.…”
Section: Experimental and Numericalmentioning
confidence: 67%
See 1 more Smart Citation
“…Same is valid for the cylindrical portion. Kılıçaslan et al [8] were reported similar results for a confined corrugated core sandwich structure; which was also a progressively collapsing structure. In their study, as a result of confining, buckling and post buckling stresses increased.…”
Section: Experimental and Numericalmentioning
confidence: 67%
“…Competitors such as corrugated structures [8][9][10][11] were also proposed having controllable macro structures in complex shapes by providing energy absorption comparable with foam-like behavior. Metallic honeycombs are also used as core material in sandwich panels [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The static and dynamic friction coefficients were set sequentially to 0.3 and 0.2 in all contact definitions. These values of friction coefficients were also previously applied and shown to yield the numerical results well agreed with the experiments . The numerical stresses on the incident bar were calculated at the same locations with the strain gages in the experimental set‐up.…”
Section: Numerical Modelsmentioning
confidence: 68%
“…The aim of the present study was to investigate the effect of the insertion of imperfect layers on the shock mode of deformation of a multilayer 1050 H14 aluminium corrugated sandwich core. The investigated sandwich core was made of corrugated fin layers and previously shown to exhibit repeatable responses to mechanical forces under compression at low and high velocities . The quasi‐static compression tests were performed at 0.0048 m/s, and the impact tests (Taylor‐like impact) were performed at 135, 150, and 200 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows trapezoidal corrugated-cores that have trapezium in shape with the angle. Kiliçaslan et al [33] do numerical studies and experimental on the quasi-static and dynamic crushing responses of multilayer trapezoidal aluminum corrugated sandwiches. …”
Section: Trapezoidalmentioning
confidence: 99%